The Existence and Origin of Multiple Equilibria in Sand‐Mud Sediment Beds. Issue 22 (21st November 2022) - Colina Alonso, A.; van Maren, D. S.; Herman, P. M. J.; van Weerdenburg, R. J. A.; Huismans, Y.; Holthuijsen, S. J.; Govers, L. L.; Bijleveld, A. I.; Wang, Z. B.
Abstract: The sediment composition of the seabed governs its mobility, hence determining sediment transport and morphological evolution of estuaries and tidal basins. Bed sediments often consist of mixtures of sand and mud, with spatial gradients in the sand/mud content. This study aims at increasing the understanding of processes driving the sediment composition in tidal basins, focusing on depositional processes. We show that bed sediments in the Wadden Sea tend to be either mud‐dominated or sand‐dominated, resulting in a bimodal distribution of the mud content where the two modes represent equilibrium conditions. The equilibria depend primarily on the sediment deposition fluxes, with bimodality originating from the dependence of suspended sand/mud concentrations on the local bed composition. Our analysis shows that bimodality is a phenomenon that is not only specific for the Wadden Sea; it can be expected for a wide range of suspended sediment concentrations and thus also in other systems worldwide. Plain Language Summary: The bottom of coastal seas is often composed of two sediment types, namely sand and mud. The evolution of the seabed, and thus of our coasts, depends on how these sediment types move. A correct representation of the spatial sand‐mud patterns in the bed is therefore essential if we want to understand and predict coastal evolution. Studying a large data set we found that sediment beds tend to be either sandy or muddy, with lower chances of finding something in between (i.e., bimodality). Although segregation of sand and mud has often been attributed to erosion processes, we found that this is mainly the result of depositional processes, and especially of the suspended sediment concentrations. Sand concentrations largely depend on local conditions, while local mud concentrations are much more affected by conditions elsewhere and/or earlier. The difference in the suspended sand and mud concentrations leads to multiple equilibria in the bed composition—resulting in the previously mentioned bimodality—for a very wide range of conditions. Therefore, we also expect bimodality and sharp sand‐mud transitions in other systems worldwide. Key Points: Mud contents in the sediment bed can be bimodally distributed, resembling preferential sand‐mud segregation Bimodality represents the existence of two stable equilibrium conditions, which are a result of the deposition fluxes of sand and mud Bimodality is expected for a large range of suspended sediment concentrations in sand‐mud systems